Deregulation Derailed: Evidence from Services Markets Liberalization in Croatia - Peter Grajzl; Bruno Ćorić; Stjepan Srhoj (Global Labor Organization (GLO), 2025)
Conventional wisdom suggests that when business regulation is excessive, deregulation should enhance efficiency. The liberalization of services markets in Croatia demonstrates that this is not necessarily the case, particularly when features of the reform process allow undue influence by those who stand to lose from the removal of regulatory barriers. To assess the effects of the Croatian reform, we determine the yearly volume of deregulation measures applicable to each affected sector and construct a sector-level panel dataset encompassing a wide range of outcomes. Exploiting within-sector, over-time variation in the volume of deregulation measures, we find that deregulation, on average, increased labor productivity but had no effect on entry, employment, or profit margins. While both new entrants and incumbents shared the labor-productivity gains, incumbents benefited more and also experienced an increase in profit margins. Heterogeneity analysis reveals that the reform was more effective in sectors with initial conditions indicative of weaker incumbent power. Our findings underscore the relevance of public-choice perspectives not only in understanding regulation, as emphasized by prior literature, but also in the context of deregulation.
Keywords: L51; L80; D02; K20; P16; 330; deregulation; liberalization; services markets; heterogeneity; special interests